Developing an E-module of Paragraph Writing Subject in a Private University Using Genre Approach - Fiani, Ani; Frima, Aren (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this paper was to develop an E-module of writing paragraph subject using genre Approach, particularly Reading to Learn. This paper used a research and development approach. The result of three expert review showed that the prototype of the product was categorized as having high validityas indicated by the average score of questionnaires on content with 4.4, the instructional design 3.9, and media (3.9). Moreover, the module was also categorized as highly practical as indicated by the average score of one-to-one evaluation (4.22) and small group evaluation (4.29). Meanwhile, the result of field test evaluation showed that there was an improvement in students writing with the mean 75.18 was the final result (post-test) which was considered as high. There was an improvement made by students after the researcher gave them a treatment by using the E-module. Keywords: E-module, Genre Approach, Narrative Paragraph, Reading to Learn, Writing Skill